Morphometry of Acromion Process of Human Scapulae and Its Clinical Importance Amongst Nepalese Population - Mansur, DI; Khanal, K; Haque, MK; Sharma, K (Kathmandu University Medical Journal, 2013)
Background Morphometry of the acromion process of the scapula is an important factor implicated in impingement syndrome of the shoulder joint. Authors who have studied this process have tried to classify it according to the standard Bigliani classification viz., type 1, 2 and 3. Objectives To analyze and classify the acromion process of human scapulae. Methods The present study was observational, cross-sectional and descriptive in nature. The present study was conducted on 68 adult human scapulae (30 right and 38 left) of unknown age and sex in the Department of Anatomy, Kathmandu University School of Medical Sciences, Dhulikhel, Nepal. The length and breadth of the acromion process and the distances from the tip of the acromion process to the uppermost point of the glenoid cavity and to the tip of the corocoid process were measured with a help of caliper and measuring tape. Results The average length of acromion process on the right and left scapulae were 46.46 ± 5SD mm and 45.57 ± 5.21 SD mm respectively. The average breadth of acromion process of right and left scapulae were 26.63 ± 3.55 SD mm and 27.23 ± 3.06 SD mm respectively. The acromio-coracoid distance on the right and left side were 39.03 + 6.20 mm and 39.39 +5.32 mm respectively. The acromio-glenoid distance was also measured which was 31.83 +3.66 mm & 31.97 +3.96 mm on right and left side respectively. The acromion process was classified in the present study into 3 types, based on the shape as: Triangular - 36.76%, Quadrangular - 52.94% and Tubular - 10.29%. Conclusions Knowing the data on the shape and various distances of acromion may not only help the orthopaedicians during surgical repair around the shoulder joint but also may be of interest to the anthropologists when studying about the evolution of the bipedal gait. The morphometric analysis of the acromion should be used like an auxiliary to promote a better knowledge about the disease that appears in this area. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 33-36 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7340